Penggunaan media simulasi pernafasan untuk meningkatkan kemampuan hasil Belajar ipa siswa sekolah dasar - Muryati, Muryati (Universitas Sebelas Maret, 2022)
The purpose of this paper is to increase the effectiveness of distance learning and students' creative thinking skills in understanding science concepts, especially about the material on the human respiratory system in Class V students at SDN Sabranglor, Surakarta City. Implementation Steps: The preparations made were to make a Learning Implementation Plan (RPP) with an innovative learning design. This learning design is designed by creating distance learning that remains active and creative. Implementation of the Learning Process: The implementation of the learning process is carried out online through the whats app group. Based on the distance learning process that has been implemented, it can be obtained that the use of